Band gap widening and quantum tunnelling effects of Ag/MgO/p-Si MOS structure. (7th October 2016) - Kamarulzaman, Norlida; Badar, Nurhanna; Chayed, Nor Fadilah; Kasim, Muhd Firdaus
Abstract: MgO films of various thicknesses were fabricated via the pulsed laser deposition method. The MgO thin films obtained have the advantage of high quality mirror finish, good densification and of uniform thickness. The MgO thin films have thicknesses of between 43 to 103 nm. They are polycrystalline in nature with oriented growth mainly in the direction of the [200] and [220] crystal planes. It is observed that the band gap of the thin films increases as the thickness decreases due to quantum effects, however, turn-on voltage has the opposite effect. The decrease of the turn-on as well as the tunnelling voltage of the thinner films, despite their larger band gap, is a direct experimental evidence of quantum tunnelling effects in the thin films. This proves that quantum tunnelling is more prominent in low dimensional structures.